Two‐energy‐scale model for description of the thermal quenching of photoluminescence in disordered Ga(As, Bi). Issue 8 (5th June 2015) - Shakfa, M. K.; Wiemer, M.; Ludewig, P.; Jandieri, K.; Volz, K.; Stolz, W.; Baranovskii, S. D.; Koch, M.; Seibt, M.
Abstract The thermal quenching of the photoluminescence (PL) intensity in Ga(As, Bi)/GaAs heterostructures is studied experimentally and theoretically. We observed an anomalous plateau in the PL thermal quenching at intermediate temperatures under low excitation conditions. Our theoretical analysis based on a well‐approved theoretical approach shows that this peculiar behavior of the temperature‐dependent PL intensity cannot be interpreted assuming a single‐scale monotonously energy‐dependent density of localized states (DOS). Experimental data clearly point at a non‐monotonous DOS with at least two energy scales. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)